Pengaruh Indeks Pembangunan Manusia, Tenaga Kerja dan Kemiskinan terhadap Pertumbuhan Ekonomi Provinsi Kalimantan Selatan Tahun 2017-2019 - Nor, Muhammad Rizkiyan; Chandriyanti, Ika (PPJP ULM, 2023)
This study has three objectives, namely (1) knowing the partial influence of HDI, labor, and poverty on the economic growth of South Kalimantan, (2) knowing the simultaneous influence of HDI, labor, and poverty on the economic growth of South Kalimantan, and (3) knowing the most dominant independent variables on the economic growth of South Kalimantan. This study uses panel data regression analysis test methods, model estimation tests, classical assumption tests, partial and simultaneous hypothesis testing, determination coefficient tests, and correlation coefficient tests operated through the EViews 9 software. The results of this study show that the HDI and labor variables partially have a significant effect, while the poverty variables have no significant impact on economic growth. As for simultaneously, independent variables have a substantial effect on dependent variables. This study shows that the HDI variable has the most dominant influence on the economic growth of South Kalimantan Province in 2017-2019.